A Comparison of the Elementary School Educational Management in Malaysia and Indonesia - Sri Marmoah; Jenny I. S Poerwanti; Siti Istiyati; Supianto; Sukarno; Hasan Mahfud (Jurnal Penelitian Pendidikan IPA, 2023)
In the development of a country, education is an important aspect and a good management system is an important factor for achieving an educational goal. Indonesia and Malaysia have similar backgrounds but these two countries have differences in terms of providing education management of elementary school. Reflecting on it, this study raises the topic of a comparison of elementary school educational management in Indonesia and Malaysia. This paper aims to compare the elementary school educational management in Malaysia and Indonesia. A qualitative approach was used in this research. Data were obtained through literature studies of books and scientific journal articles that pay attention to their relevance.Â  Data analyzed by comparative analysis. The results show education management planning, organizing, actuating, and controlling in both countries that have differences and similarities. This study shows the actualization of elementary educational management in these two countries and hopefully this study can recommend improvements in terms of education management. Â  Â